G(q)-dependent signalling by the lysophosphatidic acid receptor LPA(3) in gastric smooth muscle: reciprocal regulation of MYPT1 phosphorylation by Rho kinase and cAMP-independent PKA - Sriwai, Wimolpak (Biochem J, 2008)
The present study characterized the signalling pathways initiated by the bioactive lipid, LPA (lysophosphatidic acid) in smooth muscle. Expression of LPA(3) receptors, but not LPA(1) and LPA(2), receptors was demonstrated by Western blot analysis. LPA stimulated phosphoinositide hydrolysis, PKC (protein kinase C) and Rho kinase (Rho-associated kinase) activities: stimulation of all three enzymes was inhibited by expression of the G(α)(q), but not the G(α)(i), minigene. Initial contraction and MLC(20) (20 kDa regulatory light chain of myosin II) phosphorylation induced by LPA were abolished by inhibitors of PLC (phospholipase C)-β (U73122) or MLCK (myosin light-chain kinase; ML-9), but were not affected by inhibitors of PKC (bisindolylmaleimide) or Rho kinase (Y27632). In contrast, sustained contraction, and phosphorylation of MLC(20) and CPI-17 (PKC-potentiated inhibitor 17 kDa protein) induced by LPA were abolished selectively by bisindolylmaleimide. LPA-induced activation of IKK2 {IκB [inhibitor of NF-κB (nuclear factor κB)] kinase 2} and PKA (protein kinase A; cAMP-dependent protein kinase), and degradation of IκBα were blocked by the RhoA inhibitor (C3 exoenzyme) and in cells expressing dominant-negative mutants of IKK2(K44A) or RhoA(N19RhoA). Phosphorylation by Rho kinase of MYPT1 (myosin phosphatase targeting subunit 1) at Thr(696) was masked by phosphorylation of MYPT1 at Ser(695) by PKA derived from IκB degradation via RhoA, but unmasked in the presence of PKI (PKA inhibitor) or C3 exoenzyme and in cells expressing IKK2(K44A). We conclude that LPA induces initial contraction which involves activation of PLC-β and MLCK and phosphorylation of MLC(20), and sustained contraction which involves activation of PKC and phosphorylation of CPI-17 and MLC(20). Although Rho kinase was activated, phosphorylation of MYPT1 at Thr(696) by Rho kinase was masked by phosphorylation of MYPT1 at Ser(695) via cAMP-independent PKA derived from the NF-κB pathway.